Caries experience and salivary aspects in individuals with fragile X syndrome - Cristhiane Olívia Ferreira do AMARAL; Fabiana Gouveia STRAIOTO; Marcelo Henrique NAPIMOGA; Elizabeth Ferreira MARTINEZ (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Fragile X syndrome (FXS) is the most common cause of hereditary mental retardation, but studies on the oral health condition of these patients are rare. The aim of this study was to determine the experience of dental caries in individuals with FXS, by examining the saliva profile, oral hygiene, socioeconomic characteristics and use of controlled drugs in these patients. Dental health was estimated using the decayed, missing and filled teeth index (DMF-T) and sialometry, and the pH value and buffering capacity of the saliva, colony forming units of S. mutans (CFU/mL), visible biofilm index, and socioeconomic status were all examined. The sample, comprising 23 individuals, had an average age of 17.3 ± 5.6 years, a DMF-T index of 5.5, a diminished salivary flow (78.3%), and a low (73.9%) saliva buffering capacity. Most (52.2%) individuals presented with a high abundance (CFU/mL) of S. mutans. The experience of caries was correlated with salivary parameters, poor oral hygiene, lower socioeconomic status and an increased count of S. mutans in saliva.